Effects of Nitrogen Addition on Nitrogen Resorption in Temperate Shrublands in Northern China. - Jianhua Zhang; He Li; Haihua Shen; Yahan Chen; Jingyun Fang; Zhiyao Tang (PLoS ONE, 2015)
Nutrient resorption from senescing leaves is a key mechanism of nutrient conservation for plants. The nutrient resorption efficiency is highly dependent on leaf nutrient status, species identity and soil nutrient availability. Nitrogen is a limiting nutrient in most ecosystems, it is widely reported that nitrogen resorption efficiency (NRE) was highly dependent on the soil nitrogen availability and vary with N deposition. The effects of nitrogen deposition on NRE and nitrogen concentration in green and senescing leaves have been well established for forests and grasslands; in contrast, little is known on how plants in shrublands respond to nitrogen deposition across the world. In this study, we conducted a two-year nitrogen addition manipulation experiment to explore the responses of nitrogen concentration in green and senescing leaves, and NRE of seven dominant species, namely, Vitex negundo, Wikstroemia chamaedaphne, Carex rigescens and Cleistogenes chinensis from the Vitex negundo community, and Spirea trilobata, Armeniaca sibirica, V. negundo, C. rigescens and Spodiopogon sibiricus from the Spirea trilobata community, to nitrogen deposition in two typical shrub communities of Mt. Dongling in northern China. Results showed that NRE varied remarkably among different life forms, which was lowest in shrubs, highest in grasses, and intermediate in forbs, implying that shrubs may be most capable of obtaining nitrogen from soil, grasses may conserve more nitrogen by absorption from senescing leaves, whereas forbs may adopt both mechanisms to compete for limited nitrogen supply from the habitats. As the N addition rate increases, N concentration in senescing leaves ([N]s) increased consistent from all species from both communities, that in green leaves ([N]g) increased for all species from the Vitex negundo community, while no significant responses were found for all species from the Spirea trilobata community; NRE decreased for all species except A. sibirica from the Vitex community and W. chamaedaphn from the Spirea community. Given the substantial interspecific variations in nutrient concentration, resorption and the potentially changing community composition, and the increased soil nutrient availability due to fertilization may indirectly impact nutrient cycling in this region.